Management of Gastrointestinal Tract Arteriovenous Malformations in Adults: A Literature Review - Ibrahim, Febiansyah; Beatrice, Angie (The New Ropanasuri Journal of Surgery, 2026)
Introduction. Arteriovenous malformations (AVMs) of the gastrointestinal (GI) tract are rare vascular lesions that can cause significant GI bleeding, posing a diagnostic challenge in clinical practice. This literature review examines the management strategies for AVMs in adults, focusing on identifying optimal treatment approaches and minimizing recurrence, particularly in Indonesia where no standardized treatment guidelines are available. Method. A literature search was conducted from August 24, 2022, to September 11, 2023, using PUBMED®, Cochrane®, Proquest®, and Scopus® databases. The inclusion criteria were studies published in English or Indonesian within the last 25 years, including case series, cohort studies, or systematic reviews involving patients with GI AVMs. The Joanna Briggs Institute Critical Appraisal Checklist was used for evaluating study quality. After screening for relevance and duplicates, 5 studies met the inclusion criteria. Result. Database search using specific keywords obtained in total of 1012 titles. Screening of titles and abstracts then 5 studies met the criteria. AVMs were reported in various anatomical locations of gastrointestinal tract. Including ileum, colon, and duodenum. Treatment strategis tailored into three major approaches: operative, non-operative (minimally invasive including interventional radiology), and medical. Transarterial embolization (TAE) which emerged as the most frequent employed and effective modality in both emergent and elective settings. Recurrence rates following TAE varied but were generally lower than those observed with conservative or incomplete interventions. Endovascular embolization also served as a valuable alternative in patients who declined surgical intervention or when lesions were inaccessible surgically. Conclusion. Advancement in endovascular interventional radiology and super-selective embolization have led to effective management of non-variceal gastrointestinal bleeding, including AVMs with minimal recurrence, though organ ischemia remains a risk. Surgical intervention is crucial when embolization fails or complications arise. Innovations in intraoperative AVM localization have improved surgical accuracy and reduced recurrrence.